Research on the Digital Transformation of Small and Medium sized Enterprises in the Context of Digital Economy - Xia, Pengcheng; Li, Feiyi; Xu, Xiao; Tao, Lei; Du, Jingyu; Niu, Niubu A; Chen, Zhou (Journal of Global Economy, Business and Finance, 2024)
With the rapid development of informatization, the global economy is gradually transitioning from traditional industrial economy to digital economy. In this context, promoting digital transformation has provided significant assistance for the development of enterprises. Currently, many small and medium-sized enterprises are also actively promoting digitalization, but still face some problems. The article briefly analyzes the motives, current situation, and problems faced by small and medium-sized enterprises in their digital transformation, and proposes corresponding countermeasures, hoping to provide reference and guidance for some enterprises.